The nucleophilic, phosphine-catalyzed thiol-ene click reaction and convergent star synthesis with RAFT-prepared homopolymers - Chan, J.; Yu, B.; Hoyle, C.; Lowe, Andrew (Elsevier Ltd, 2009)
The synthesis of 3-arm star polymers from reversible addition-fragmentation chain transfer (RAFT)-prepared precursor homopolymers in combination with thiol-ene click chemistry is described. Homopolymers of n-butyl acrylate and N,N-diethylacrylamide were prepared with 1-cyano-1-methylethyl dithiobenzoate and 2,2'-azobis(2-methylpropionitrile) yielding materials with polydispersity indices (Mw/Mn) = 1.18 and controlled molecular weights as determined by a combination of NMR spectroscopy, size exclusion chromatography (SEC), and matrix assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS). Subsequent one-pot reaction of homopolymer, hexylamine (HexAM), dimethylphenylphosphine (DMPP), and trimethylolpropane triacrylate (TMPTA) results in cleavage of the thiocarbonylthiol end-group (by HexAM) of the homopolymer yielding a macromolecular thiol that undergoes DMPP-initiated thiol-Michael addition to TMPTA yielding 3-arm star polymers. The presence of DMPP is demonstrated to serve an important second role in effectively suppressing the presence of any polymeric disulfide as determined by SEC. Such phosphine-mediated thiol-ene reactions are shown to be extremely rapid, as verified by a combination of FTIR and NMR spectroscopies, with complete consumption of the C{double bond, long}C bonds occurring in a matter of min. MALDI-TOF MS and SEC were used to verify the formation of 3-arm stars. A broadening in the molecular weight distribution (Mw/Mn ~ 1.35) was observed by SEC that was attributed to the presence of residual homopolymer and possibly 2-arm stars formed from trimethylolpropane diacrylate impurity. Interestingly, the MALDI analysis also indicated the presence of 1- and 2-arm species most likely formed from the fragmentation of the parent 3-arm star during analysis. Finally, a control experiment verified that the consumption of C{double bond, long}C bonds does not occur via a radical pathway. © 2009 Elsevier Ltd. All rights reserved.